Effect of long-chain omega-3 polyunsaturated fatty acids on cardiometabolic factors in children with acute lymphoblastic leukemia undergoing treatment: a secondary analysis of a randomized controlled trial - Barbosa-Cortes, Lourdes; Atilano-Miguel, Salvador; Martin-Trejo, Jorge Alfonso; Jiménez-Aguayo, Emmanuel; Martínez-Becerril, Fabian Ismael; López-Alarcón, Mardia; Mejía Aranguré, Juan Manuel; Maldonado-Hernández, Jorge; Delgadillo-Portillo, Suyly; Guzmán-Castro, Brenda; Delgadillo-Portillo, Jazmín; Añoveros-Barrera, Ana; et al. (Frontiers in Endocrinology, 2023)
Increased triglycerides (TGs) are a major risk factor for cardiovascular disease. Furthermore, hypertriglyceridemia is commonly associated with a reduction of high-density lipoprotein cholesterol (HDL-C) and an increase in atherogenic small-dense low-density lipoprotein (LDL-C) levels. Studies provide support that polyunsaturated omega-3 fatty acids (ω3-LCPUFAs) are cardioprotective and have antithrombotic and anti-inflammatory effects. The potential effects of ω3-LCPUFAs on cardiometabolic factors and anti-inflammatory actions in children with acute lymphoblastic leukemia (ALL) are limited. This is a secondary analysis of a previous clinical trial registered at clinical trials.gov (# NCT01051154) that was conducted to analyze the effect of ω3-LCPUFAs in pediatric patients with ALL who were receiving treatment. Objective: To examine the effect of supplementation with ω3-LCPUFAs on cardiometabolic factors in children with ALL undergoing treatment. Intervention: Thirty-four children (placebo group: 20 patients; ω3-LCPUFAs group: 14 patients) aged 6.7 ± 2.7 years who were newly diagnosed with ALL were evaluated. Children were randomized to receive either ω3-LCPUFAs or placebo capsules (sunflower oil). ω3-LCPUFAs were administered in the form of 500-mg soft capsules. The ω3-LCPUFA capsules contained 225 mg of DHA, 45 mg of EPA, and 20 mg of another ω3-LCPUFAs. The omega-3 dose was administered at a rate of 0.100 g/kg of body weight/day for three months. Main outcomes: Fasting cholesterol, HDL-C, very-low-density lipoprotein (VLDL-C), TGs, atherogenic index of plasma (AIP), android/gynoid ratio (A/GR), IL-6, TNF-α, and percentage of fat mass (DXA) were measured in all patients. Fatty acid analyses in red blood cells were performed with gas chromatography. Results: We found significantly lower levels of TGs (p=0.043), VLDL-C (p=0.039), IL-6 (p=0.025), and AIP (p=0.042) in the ω3-LCPUFAs group than in the placebo group at three months. In contrast, the total cholesterol concentration was higher at 3 months in the ω3-LCPUFAs group than in the placebo group (155 mg/dl vs. 129 mg/dl, p=0.009). The number of children with hypertriglyceridemia (85% vs. 50%; p=0.054) tended to be lower between the time of diagnosis and after 3 months of supplementation with ω3-LCPUFAs. Conclusion: These findings support the use of ω3-LCPUFAs to reduce some adverse cardiometabolic and inflammatory risk factors in children with ALL.